2015
DOI: 10.1542/peds.2014-2978
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use in Films and Adolescent Alcohol Use

Abstract: OBJECTIVES: To investigate whether exposure to alcohol use in films (AUFs) is associated with early alcohol use, binge drinking, and alcohol-related problems in British adolescents.METHODS: Cross-sectional study with 5163 15-year-olds from the Avon Longitudinal Study of Parents and Children in the United Kingdom. We measured adolescent exposure to AUFs, age at onset of alcohol use, and binge-drinking behavior. We adjusted for early childhood social, family and behavioral factors, adolescent tobacco use, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Our study is the first to confirm the association between AUF and drinking behavior in adolescents from Latin America. Our results are consistent with studies conducted in other countries (Hanewinkel and Sargent, ; Hanewinkel et al., , ; Sargent et al., ; Waylen et al., ; Wills et al., ). Although our study suggested different mean levels of exposure to AUF in Argentina and Mexico than for adolescents from the United States (median 8.6 hours) (Sargent et al., ), or Germany (median 3.4 hours) (Hanewinkel et al., ), we found a similar dose–response association between exposure to AUF and alcohol use, engagement in binge drinking, and alcohol susceptibility.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is the first to confirm the association between AUF and drinking behavior in adolescents from Latin America. Our results are consistent with studies conducted in other countries (Hanewinkel and Sargent, ; Hanewinkel et al., , ; Sargent et al., ; Waylen et al., ; Wills et al., ). Although our study suggested different mean levels of exposure to AUF in Argentina and Mexico than for adolescents from the United States (median 8.6 hours) (Sargent et al., ), or Germany (median 3.4 hours) (Hanewinkel et al., ), we found a similar dose–response association between exposure to AUF and alcohol use, engagement in binge drinking, and alcohol susceptibility.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental studies have shown that alcohol portrayals in films directly influence actual alcohol intake, presumably by imitation and cue‐reactivity processes (Engels et al., ; Koordeman et al., ). Finally, cross‐sectional and longitudinal associations have been reported for the relationship between exposure to alcohol use in films (AUF) and alcohol use and binge drinking among adolescents in the United States, England, and Germany (Dal Cin et al., ; Hanewinkel and Sargent, ; Hanewinkel et al., , , ; Morgenstern et al., ,b, ; Nunez‐Smith et al., ; Sargent et al., ; Waylen et al., ). That alcohol companies pay for alcohol brand placement in films is important, because it means that film alcohol depictions could be reduced if payments were restricted, as was the case with smoking in films (Bergamini et al., ).…”
mentioning
confidence: 99%
“…Prior research has shown that both media and peers are strong influences on youth substance use behaviors and attitudes, and YouTube is known to be a popular social media site among teens (Allen et al, 2012; Mander, 2015; Salimian et al, 2014; Wasserman, 2013; Waylen et al, 2015), therefore the accessibility of edibles-related videos to underage youth is of concern. Specifically, we found that, similar to other studies about substance use on YouTube (Barry et al, 2015; Huang, Kornfield, & Emery, 2016; Seidenberg, Rodgers, Rees, & Connolly, 2012; Winpenny, Marteau, & Nolte, 2014), the majority of videos about edibles was accessible to underage viewers.…”
Section: Discussionmentioning
confidence: 99%
“…Media and peer influences are some of the most important factors affecting substance use among young people (Allen, Chango, Szwedo, Schad, & Marston, 2012; Salimian, Chunara, & Weitzman, 2014; Waylen, Leary, Ness, & Sargent, 2015). YouTube is the most popular video-sharing website, and includes both originally created videos and shows/video clips from television.…”
mentioning
confidence: 99%
“…Children’s health beliefs and behaviors are associated with their media exposure, and this has been empirically demonstrated for alcohol use, 14 smoking, 5,6 and violence. 7,8 Although the sedentary nature of media consumption is likely one reason for the relationship between media and obesity, another possible mechanism is media-based exposure to food and beverage content that promotes high-calorie, low-nutrient foods and beverages.…”
Section: Introductionmentioning
confidence: 98%